Impact of government sectoral expenditure on economic growth in Malawi, 1980-2007 - Musaba, Emmanuel; Chilonda, Pius; Matchaya, Greenwell C. (2013)
This paper examines the impact of government sectoral expenditure on economic growth in Malawi. Using time series data from 1980 to 2007, cointegration analysis in the context of an error correction model was employed to estimate the growth effects of government expenditures in agriculture, education, health, defence, social protection and transport and communication. The short run results showed no significant relationship between government sectoral expenditure and economic growth. The long run results showed a significant positive effect on economic growth of expenditure on agriculture and defence. The expenditures on education, health, social protection and transportation and communication were negatively related to economic growth. To boost economic growth efficient management of resources allocated to all sectors should be emphasized.